EU countries migration policies with external dimension - Demirbas, İ. Ferhat (Lviv Polytechnic Publishing House, 2016)
The migration phenomena in the Mediterranean and in the Middle East have a great importance on immediate needs. For that reason EU’s migration policy should intensify cooperation with neighbour and third countries. The current situation creates an opportunity for the EU to form a robust policy for determination of the right balance in its migration policy. However this policy migration might be managed by all EU actors internal and external. In this context this study will focus on EU policy for refugees and visa. With this focus it will be tried to determine a profile for migration policy in order to make recommendations for solving migration issues in EU, neighbour countries and third countries. This study will try to come to a result focusing on sending and transit countries, and enhancing policy coherence on migration between the EU and its member states.
Keywords: EU; Migrations; Internatioanal Relations; Middle East